Pencirian Mananase Streptomyces costaricanus 451-3 - Anjani Meryandini; Dwi Ambarawati; Nisa Rachmania (Jurnal Ilmu Pertanian Indonesia, 2008)
Major component of hemicelluloses are mannans (softwoods) and xylans (hardwoods). Hemicclluloses arc used by microbes as a carbon sources. Mannanase and xylanasc arc enzyme complex that are able to degrade hemicelluloses. Mannanase activity from Streptomyces costarianus 451-3 was tested in locust bean gum 0.5% and coconut meal 0.5% medium and was detected by dinitrosalysilic acid method. Protein concentration was measured using Bradford method. Mannanase and xylanase activity were also detected using birchwood xylan and oatspelt xylan medium. The optimum temperature and pH of Streptomyces mannanase strain 451-3 was 40 oC and 6,0, respectively. The addition 1mM of Mg2+ and Zn2+ at final concentration increased the mannanase activity for about 30% and 80%, while 1mM Mn2+, Ca2+ and Co2+ decreased its activity for about 67%, 100%, and 60%, respectively. The addition of I mM ethylene diamine tetraacetic acid tend to decreased the enzyme activity to 30%. The medium which contain birchwood xylan dan oatspelt xylan could induce mannanase activity, hut in a lower degree then that of xylanase. Keywords: mananase, streptomyces, xilanasc